Unsaturated 10H2DA Queen Bee Acid from Royal Jelly Modulates Epithelial-to-Mesenchymal Transition in SW-480 Colorectal Cancer Cells - Milena M. Jovanović; Dragana S. Šeklić (Biology and Life Sciences Forum, 2025)
Cancer research largely focuses on epithelial-to-mesenchymal transition (EMT) as a critical mechanism required for the formation of metastases. This process involves the transformation of epithelial cells into mesenchymal cells by acquiring suppressed levels of anti-EMT and elevated expression of pro-EMT markers. Unsaturated fatty acid 10H2DA has not been investigated hitherto regarding its potential to target specific EMT markers in colorectal cancer (CRC). In our study, this substance showed successful upregulation of the expression of the anti-EMT marker E-cadherin and downregulation of the expression of pro-EMT markers SNAIL, N-cadherin, and Vimentin at the gene and protein levels. This prominent effect of 10H2DA in modulating the expression of specific and significant EMT markers in CRC should not be neglected in future studies regarding anticancer therapeutic approaches.